A Gravity Model of Workers' Remittances - Lueth, Erik (IMF Working Papers; Working Paper ;, 2006)
This paper creates the first dataset of bilateral remittance flows for a limited set of developing countries and estimates a gravity model for workers' remittances. We find that most of the variation in bilateral remittance flows can be explained by a few gravity variables. The evidence on the motives to remit is mixed, but altruism may be less of a factor than commonly believed. Most strikingly, remittances do not seem to increase in the wake of a natural disaster and appear aligned with the business cycle in the home country, suggesting that remittances may not play a major role in limiting vulnerability to shocks. To encourage remittances and maximize their economic impact, policies should be directed at reducing transaction costs, promoting financial sector development, and improving the business climate.